Nutrition in Britain in the twentieth century - Smith, David Frederick (University of Edinburgh, 1986)
The study is initially concerned with the origins and development of different approaches to nutrition science in Britain during the first three decades of the twentieth century. The contrasting approaches are shown to embody alternative "styles of thought" in the sense used by Karl Mannheim. An account of the work of the Advisory Committee on Nutrition of the Ministry of Health (founded 1931) is then given. The conflicts which occurred during the deliberations of the Committee are interpreted as conflicts between those who advanced the contrasting "styles of thought. " The focus of attention then shifts to the foundation and development of the Nutrition Society (1941). The disputes which occurred in the Nutrition Society during its early years are shown to be largely concerned with alternative notions of the application of nutritional knowledge. Developments in the Society after the war, it is suggested, must be understood against the background of the post-war reaction against the "social relations of science movement". The foundation of the first Nutrition Degree in 1953 at the Nutrition Department at Queen Elizabeth College of the University of London, is then considered. A hypothesis is presented which suggests an explanation of certain important features of the professional ideology of nutrition which has been associated with the College.
Keywords: Medical; care; Medicine